English from Scratch: Preadolescents’ Developing Use of English Lexical Resources in Belgian Dutch - Schuring, Melissa; Zenner, Eline (Frontiers in Communication, 2022)
Working within the framework of the socio-pragmatic turn in anglicism research, this paper adds a developmental sociolinguistic perspective in investigating preadolescents’ use of English lexical resources in Belgian Dutch. The so far largely undocumented role of English in the linguistic transition from childhood to adolescence is analyzed through a fieldwork corpus of 15,465 utterances, collected during sociolinguistic interviews with 26 (12 boys, 14 girls) Belgian Dutch preadolescent (6–13 y/o) respondents from a local hockey club. All English lexical material in the corpus was identified and categorized following a three-step identification protocol. This protocol introduces a distinction between recognizable unavoidable English (RUE) and recognizable avoidable English (RAE). Results reveal that, overall, 9.7% of the utterances contain recognizable English (RUE+RAE), with RUE being significantly more frequent than RAE. Our findings further indicate only limited stratification according to traditional socio-demographic parameters and display a number of outliers in the respondent profiles. Closer inspection of these outliers allows the conclusion that in the community of practice studied, English is an emerging youth language marker, typically used when talking about gaming or girl-oriented activities. In sum, we conclude that preadolescents in our sample instrumentalize English for incipient identity work, both on the micro-level (being a gamer, a soon-to-be teenage girl) as on the macro-level (through ingroup and outgroup marking).